School–Parent Partnership Strategies to Support Students’ Transition to Junior High School (A Case Study at SDN Tegallega 1 and SDN Murnisari, Cianjur Regency) - Mirawati Mirawati; Hanafiah Hanafiah (Journal of Science and Education (JSE), 2026)
This study examines school–parent partnership strategies in supporting students’ transition from primary school to junior high school in two contrasting settings: SDN Tegallega 1 (urban) and SDN Murnisari (rural) in Cianjur Regency, Indonesia. Although national policies mandate family engagement and 12-year compulsory education, partnership practices at the school level are often still incidental, one-way, and not explicitly directed at preparing parents—academically, financially, and psychologically—to accompany their children to the next level. Using a qualitative multiple case study design, data were collected through in-depth interviews, participant observation, and document analysis. The findings show that both schools implemented partnership strategies consisting of joint program planning, parenting activities, learning assistance, and intensive communication through school committees. However, contextual differences shaped the emphasis: the urban school prioritized academic preparation and PPDB literacy, while the rural school emphasized motivation, moral support, and access facilitation. The study concludes that school–parent partnerships that are planned, participatory, and sustained can increase students’ readiness to continue to junior high school and strengthen positive relations among schools, parents, and students. The study recommends formalizing partnership programs in school work plans and developing two-way communication mechanisms tailored to local socio-economic conditions.